Laser asymmetric ablation method to improve corneal shape - Agudo, José Alberto Rodríguez; Park, Jinyoung; Park, Jina; Lee, Seongsu; Park, Kisung (Lasers in Medical Science, 2019)
This study aims to assess whether central-symmetric corneal thickness reduces off-centered corneal shift caused by intraocular pressure (IOP). In this retrospective study, 122 healthy eyes of 62 presbyopic patients, mostly myopic, were divided into two groups. Two distinct asymmetric corneal ablations were applied in peripheral presbyopia correction to produce central-symmetric corneal thickness, which reduces the off-centered corneal shift by utilizing intraocular pressure. The first method used a 90° angled combination in group 1 and the second method used a 45° angled combination in group 2. Target refraction was spherical equivalent of − 1D. Self-developed image processing algorithm analyzed the change in thickness and the posterior cone, and obtained two factors: central symmetry (f) and visual axis deviation (d), from each eye’s pre and postoperative maps of Orbscan II. UDVA and UNVA were also analyzed. In both groups, mean SE was about − 1D and there was no significant difference in UDVA. UNVA was better in group 2 than group 1. Only in group 2, corneal thickness and posterior cone became central-symmetric and the posterior corneal apex point relocated towards the visual axis. The p values were 0.03, 0.04, and 0.03, respectively. This is the first study to control corneal shape by utilizing the interaction between intraocular pressure and corneal thickness. Only group 2 was applied with asymmetric corneal ablation created by the 45° angled combination of semi-cylindrical ablation patterns, and intraocular pressure contributed significantly to reduce the off-centered corneal shift and reshaped the posterior corneal cone to the center.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Asymmetric corneal ablation; Central-symmetric corneal thickness; Laser asymmetric keratectomy; Semi-cylindrical ablation